Transport Authorities and Innovation: Understanding Barriers for MaaS Implementation in the Global South - Hasselwander, Marc (2022)
Mobility-as-a-Service (MaaS) is a recent concept that is seeing increasing interest across the world. First studies and field trials in developed cities suggest that MaaS can influence people's mobility behavior and create more sustainable transport systems. However, many findings are not transferable to the Global South context, considering that in terms of transport infrastructure, institutional setups, and citizens' preferences, most developing cities present significantly different characteristics. Thus, many critical questions remain unanswered, e.g., 'How to implement MaaS in a developing context?', 'What are the main challenges?', and 'Who should lead this development?'. This research work considers a public-pushed development and aims to shed light on barriers that transport authorities might face. First, barriers are identified through a literature review at the intersection of transport research and public sector innovation. Second, the barriers are analyzed based on the technology, organization, and environment (TOE) framework. Third, Global South relevance is determined through a two-round expert survey. Data related issues (e.g., standardized open data) have been identified as the most critical barrier. Also, multimodal transport planning and coordinating intermodal trips seem to be crucial challenges, considering highly fragmented operator landscapes and the lack of integrated transport planning approaches. In addition, auto-centric developments, current institutional setups, and transport authorities' organizational structures could hamper a MaaS transition in the Global South. This article contributes to the emerging literature on MaaS governance and provides insights on the capabilities of developing cities to establish MaaS and other transport innovations.